CEO OVERCONFIDENCE, ESG DISCLOSURE, AND FIRM RISK - Indah Sumunar, Kurnia; Djakman, Chaerul D (UI Scholars Hub, 2020)
Environmental, Social, and Governance (ESG) has increasingly attracted the attention of firms and stakeholders. The purpose of this study is to examine whether the mediating role of ESG disclosure has a negative effect on CEO overconfidence and firm risk, especially based on investors' perspectives. Many studies on ESG disclosure were conducted in Europe and America. Most ESG disclosures are measured using manual checklist based on annual reports or firm websites. By using panel dataset of 225 manufacturing firms in Indonesia, Malaysia, the Philippines, Singapore and Thailand from 2012-2016 obtained from Thomson Reuters’ ESG score, the research shows that CEO overconfidence has no negative direct effect on firm risk but the role of ESG disclosure as a mediating variable has a negative effect on CEO overconfidence and firm risk. CEO overconfidence has a positive effect on ESG disclosure and ESG disclosure has a negative effect on firm risk. CEO with overconfidence characteristics will make the best decisions to disclose ESG in order to increase firm value and reduce firm risk.